The European Youth Guarantee: Labor market context, conditions and opportunities in Italy - Francesco Pastore (IZA Journal of European Labor Studies, 2015)
This essay aims to discuss the conditions for a successful implementation of the European Youth Guarantee in Italy. In principle, the program should be able to affect the frictional and mismatch components of unemployment, if not the Keynesian and neoclassical ones, as the experience of Scandinavian countries suggests. However, this requires an in-depth transformation of the entire school-to-work transition system, involving not only public employment services, but also educational and training systems. To tackle the Keynesian and neoclassical components of unemployment, instead, it is vital to rethink European austerity and reduce the labor wedge.
Keywords: E12; E62; H52; J13; J24; 330; European youth guarantee; European social model; School-to-work transition; Youth unemployment; Youth experience gap; Keynesian unemployment; Neoclassical unemployment; Mismatch and frictional unemployment; Italy